2009
DOI: 10.1149/1.3129245
|View full text |Cite
|
Sign up to set email alerts
|

Star-Shaped Polymer Electrolyte with Microphase Separation Structure for All-Solid-State Lithium Batteries

Abstract: A star-shaped copolymer, poly͑styrene͒-block-poly͓poly͑ethylene glycol͒ methyl ethyl methacrylate ͑PS-block-PPEGMA 2 ͒ 8 , was synthesized by the combination of living anionic polymerization of styrene and ruthenium-catalyzed living radical polymerization of poly͑ethylene glycol͒ methyl ether methacrylate. The prepared star-shaped copolymer was characterized to evaluate its use as a solid polymer electrolyte ͑SPE͒ in lithium-ion batteries. The star polymer comprised a hard, condensed poly͑styrene͒ part at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 29 publications
0
61
0
Order By: Relevance
“…Fig. 14 [148][149][150][151][152][153][154][155][156][157] shows that the conductivities of other solid polymer electrolytes are typically in the same range as those of PEO, which is indicated by the broken lines. Electrolytes containing ethylene oxide, such as poly(ethylene oxide) methyl ether methacrylate (PEOMA) [148] and poly(acetyl-oligo(ethylene oxide) acrylate) (PAEOA) [149], or poly(ethylene glycol) (PEG), such as polyester diacrylate (PEDA)-PEG copolymers [150], poly(ethylene glycol) dimethacrylate (PDE) [152], poly(ethylene glycol) methacrylate (PME) [152], poly(ethylene glycol) methyl ether methacrylate (PEGMA) [153] and tri(ethylene glycol) diacrylate (TEGDA) [152], have conductivities in the range of, or even higher than, PEO.…”
Section: Solid Polymer Electrolytesmentioning
confidence: 99%
“…Fig. 14 [148][149][150][151][152][153][154][155][156][157] shows that the conductivities of other solid polymer electrolytes are typically in the same range as those of PEO, which is indicated by the broken lines. Electrolytes containing ethylene oxide, such as poly(ethylene oxide) methyl ether methacrylate (PEOMA) [148] and poly(acetyl-oligo(ethylene oxide) acrylate) (PAEOA) [149], or poly(ethylene glycol) (PEG), such as polyester diacrylate (PEDA)-PEG copolymers [150], poly(ethylene glycol) dimethacrylate (PDE) [152], poly(ethylene glycol) methacrylate (PME) [152], poly(ethylene glycol) methyl ether methacrylate (PEGMA) [153] and tri(ethylene glycol) diacrylate (TEGDA) [152], have conductivities in the range of, or even higher than, PEO.…”
Section: Solid Polymer Electrolytesmentioning
confidence: 99%
“…The cation transport is assisted by segmental motion of the polymer chains. Recognizing the fact that ion conduction takes place in the amorphous phase of polyethylene oxide, considerable research has focused on tailoring a flexible host polymer chemical structure with larger proportion of amorphous phase such as PEO-based block copolymers [8,9], star-branched copolymers [10,11] and cross-linked network polymers [12]. Blending is also an effective method to improve the performance of PEO-based electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…When doped with LiBC 4 O 8 (LiBOB), the copolymer electrolyte is a transparent, flexible film with an ionic conductivity of 1 9 10 -5 S/cm, lithium transference of 0.9 and electrochemical stability above 5 V at room temperature. Niitani et al (2009) reported a polystyrene (PS)-block-polyethylene glycol methyl ethyl methacrylate (PPEGMA) 2 star-shaped copolymer with a PS core and PPEGMA arms. When doped with LiBETI, the star copolymer electrolyte is a flexible film with a total ionic conductivity in the order of 10 -4 S/cm at room temperature.…”
Section: Polymer Electrolytesmentioning
confidence: 99%